Battery Construction From Lime Orange - Ricky Andi Syahputra; Siti Rahmah; Minda Shafina Syafei; Firda Nur Hidayah; Maria Enjelita Simanjuntak; Robeka Hutasoit; Yonas Alexandry Sitorus; Zeny Afriska Barutu (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
Acidic battery electrolytes, thus fruits that are acidic and contain lots of KCl can be used as an alternative to Citrus or orange electrolytes is one type of fruit that is famous for its acidity because it contains a lot of citric acids (C6H8O7). Oranges also contain calcium, phosphorus, and iron. Another advantage of citrus fruit is its abundant availability, and the waste of orange peel also has acid content, which can also be used as a bio-battery material. It concluded that lime could flow electric current because it contains chemicals such as citric acid, amino acids, glycosides, and calcium: phosphorus. Lime is a lot of ingredients and benefits that are useful for our health. Besides, lime contains chemical elements. Chemical elements found in lime can produce an electric current because it contains citric acid, amino acids, glycosides, phosphorus, etc. Thus, the lime can turn on the lights after being connected in series.